Strategy To Increase Participation of Palm Oil Enterprises in Registering Casual Laborers To Labor Social Security Program - Manalu, Joy Pangeranto; Anggraini Sukmawati; Cahyadi, Eko Ruddy (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Many new positions in palm oil plantations and mills are for casual laborers who are particularly vulnerable to poor earnings, lack of social security, and limited legal support. This study purpose is to identify the alternative strategy that can be taken by BPJS Ketenagakerjaan to increase the number of casual laborers in oil palm plantations who enroll in the labor social security program. Purposive sampling is utilized to collect primary data for this study. Respondents are interviewed and given paper-based questionnaires. The respondents are five experts involved in BPJS Ketenagakerjaan's planning and strategy decision-making processes, specifically the Investigating Supervisory Officer (Petugas Pengawas Pemeriksa), Head of Branch Office, Deputy Director of DKI Jakarta Region, Deputy Director for Corporate and Institutional Membership, and Deputy Director for Special Membership. The results of the questionnaire were processed using Expert Choice 11, based on Analytic Hierarchy Process (AHP) as the analytical tool for this study. The results of this study suggest that BPJS Ketenagakerjaan can employ a law enforcement strategy to increase company compliance as an alternative strategy so that casual laborers are able to enroll in the labor social security program. Keywords: AHP, BPJS Ketenagakerjaan, casual laborers, labor social security, oil palm plantation